"It was an Emotional Baby": Previvors' Family Planning Decision‐Making Styles about Hereditary Breast and Ovarian Cancer Risk. Issue 6 (30th January 2017) - Dean, Marleah; Rauscher, Emily A.
Abstract: Women who test positive for a BRCA genetic mutation are at an increased risk for developing hereditary breast and ovarian cancer and have a 50% chance of passing on their genetic mutation to their children. The purpose of this study was to investigate how women who test positive for a BRCA mutation but have not been diagnosed with cancer make decisions regarding family planning. Analysis of interviews with 20 women revealed they engage in logical and emotional decision‐making styles. Although women want to be logical to reduce their hereditary cancer risk, emotions often complicate their decision‐making. Women experience fear and worry about a future cancer diagnosis, yet also desire to create a family, particularly having children through natural conception. That is, women negotiate having preventative surgeries in a logical doctor‐recommended timeframe but also organize those decisions around emotional desires of motherhood. Overall, this study demonstrates the complex decisions women who test positive for a BRCA mutation must make in regards to genetic testing timing, family planning, and overall quality of life.